Identification of antigenic epitopes in a surface protein antigen of Streptococcus mutans in humans. - Matsushita, K (1994)
The reactivities of antibodies in human serum and saliva to a cell surface protein antigen (PAc) of Streptococcus mutans and synthetic peptides covering the PAc molecule were examined. Both an enzyme-linked immunosorbent assay (ELISA) and Western blotting (immunoblotting) showed that all the serum samples from five adult subjects harboring serotype c S. mutans in their oral cavity reacted with recombinant PAc (rPAc). On the other hand, the serum from a 4-month-old infant did not react with rPAc in ELISA. The immunoglobulin A (IgA) antibodies in saliva samples from the five adult subjects reacted with rPAc. However, in saliva samples from these subjects, the titers of IgA antibody to rPAc did not correlate with the titers of serum antibody to the antigen. To map continuous antigenic epitopes in the PAc molecule, we synthesized 153 decapeptides covering the entire mature PAc molecule, 121 overlapping decapeptides covering the alanine-rich repeating region (A-region) of the PAc molecule, and 21 overlapping decapeptides covering the middle region (residues 824 to 853) according to multiple pin-coupled peptide synthesis technology. Of 153 decapeptides covering the mature PAc, 27 decapeptides showed a strong reaction with the antibodies in serum from the adult subjects. The epitope-scanning patterns in the serum samples from these subjects were also very similar to each other. The antigenic epitope patterns in the saliva resembled those in the serum. However, the ELISA titers of salivary IgA antibodies to these decapeptides differed from the titers of the serum antibody. Of the 121 overlapping decapeptides covering the A-region, 27 decapeptides showed a positive reaction with the antibodies in serum from the adult subjects. All of these 27 decapeptides had either one or two of the five common sequences YQAXL, NADAKA, VQKAN, NNAKNA, and IKKRNA. Six decapeptides of the 21 overlapping decapeptides covering the middle region reacted strongly with the serum antibodies from a high PAc responder, and each of the six decapeptides had one of the two common sequences KVTKEKP and VKPTAPTK. These epitopes might therefore be relevant to the humoral responses against the PAc protein during natural infection with S. mutans in humans.